A versatile Agrobacterium-based plant transformation system for genetic engineering of diverse citrus cultivars - Dominguez, Michelle M.; Padilla, Carmen S.; Mandadi, Kranthi K. (Frontiers in Plant Science, 2022)
Developing an efficient transformation system is vital in genetically engineering recalcitrant crops, particularly trees. Here, we outline an Agrobacterium tumefaciens-based stable plant transformation methodology for citrus genetic engineering. The process was optimized to suit the requirements of fourteen citrus varieties by establishing appropriate infection, co-cultivation, selection, and culture media conditions. The procedure includes transforming seedling-derived epicotyl segments with an A. tumefaciens strain, then selecting and regenerating transformed tissues. Transgenic shoots were further identified by a visual reporter (e.g., β-glucuronidase) and confirmed by Northern and Southern blot analysis. Transgene integrations among the transgenic lines ranged between one to four. The methodology can yield transformation efficiencies of up to 11%, and transgenic plants can be recovered as early as six months, depending on the variety. In addition, we show that incorporating A. tumefaciens helper virulence genes (virG and virE), spermidine, and lipoic acid in the resuspension buffer before transformation improved the transformation efficiency of specific recalcitrant cultivars, presumably by enhancing T-DNA integration and alleviating oxidative stress on the explant tissues. In conclusion, the optimized methodology can be utilized to engineer diverse recalcitrant citrus varieties towards trait improvement or functional genetics applications.